2021
DOI: 10.1111/jocs.15888
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extracorporeal membrane oxygenation in influenza versus COVID‐19 during the first wave of COVID‐19

Abstract: Purpose: Extracorporeal membrane oxygenation (ECMO) is a refractory treatment for acute respiratory distress syndrome (ARDS) due to influenza and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, also referred to as coronavirus disease 2019 ). We conducted this study to compare the outcomes of influenza patients treated with veno-venous-ECMO (VV-ECMO) to COVID-19 patients treated with VV-ECMO, during the first wave of COVID-19.Methods: Patients in our institution with ARDS due to COVID-19 or influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 39 publications
(102 reference statements)
0
12
2
Order By: Relevance
“…, 21. , 22. In a study from Germany, Jӓckel et al 16 compared 15 COVID ECMO patients against 47 influenza ECMO patients and found a numerically, but not statistically significantly, higher hospital survival in the influenza group versus the COVID group: 57.4% vs. 40.0%; p = 0.238.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 21. , 22. In a study from Germany, Jӓckel et al 16 compared 15 COVID ECMO patients against 47 influenza ECMO patients and found a numerically, but not statistically significantly, higher hospital survival in the influenza group versus the COVID group: 57.4% vs. 40.0%; p = 0.238.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO duration was significantly longer in the COVID group: 14 days vs. 10.5 days; p = 0.0038. Finally, Blazoski et al 22 compared 28 COVID ECMO cases to 17 influenza ECMO cases. A comparison of duration of pre-ECMO mechanical ventilation was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blazoski et al noted in their literature review how poor the overall mortality of COVID-ARDS was compared to influenza-ARDS [37]. For instance, those admitted to the ICU with COVID have a 3.7 times higher risk of death than those who are admitted for influenza.…”
Section: Introductionmentioning
confidence: 99%
“…8 There have been conflicting results when comparing the outcome of ECMO support in COVID 19 patients and those with ARDS related to other viral disease. [9][10][11][12][13][14][15] The primary objective of this study was to compare the outcome of ECMO treatment in COVID 19 and influenza patients referred to a tertiary care center.…”
Section: Introductionmentioning
confidence: 99%